The Development of a Model to Enhance Teacher Leadership in Middle Schools in Shanxi Province, China - Li, Xiaotian; Asavisanu, Poonpilas (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
Teacher leadership is the heart of the transformation of a school. Teacher leaders are essential in driving change, supporting colleagues, and helping students towards academic success. Education reform in China has included strategies for developing teacher leadership. However, at the school level, there still needs to be more research and understanding of the concept in many areas. This study aimed to develop a teacher leadership model for middle school teachers in Shanxi Province, China. The study utilized exploratory mixed methods with both qualitative and quantitative analysis to develop an instrument that was subsequently used for data collection from 825 middle school teachers. By using regression analysis and interviews, elements of the model were confirmed, and it was found that to develop teacher leadership in the target middle schools, the following concepts need to be encouraged: principal leadership, peer relationships, professionalism, and leadership skills. In addition, promoting teacher leadership requires the cooperation and support of teachers, school principals, and governmental regulators. Recommendations included promoting decentralized leadership structures within schools to provide opportunities for teacher input into school policy, curriculum, and professional development. For teachers, it is essential to recognize their dual roles as "teachers" and "leaders" to encourage their participation in school management.